KAJIAN SISTEMATIS IMPLEMENTASI GAME-BASED LEARNING PADA PEMBELAJARAN MATEMATIKA DAN KAITANNYA DENGAN MOTIVASI BELAJAR - Noviyanty Sitanggang; Heni Pujiastuti; Yuyu Yuhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to systematically examine the implementation of Game-Based Learning (GBL) in mathematics learning and analyze its relationship with students’ learning motivation. The method used is a Systematic Literature Review (SLR) with the PRISMA protocol through searches in Google Scholar, Publish or Perish, and Scopus databases within the last 10 years. From the selection process, 11 scientific articles met the inclusion criteria and were analyzed using qualitative descriptive techniques and thematic synthesis. The results indicate that GBL, both digital-based and traditional game-based, consistently improves students’ learning motivation, as evidenced by increased activeness, enthusiasm, engagement, and persistence in solving mathematical problems. In addition, GBL is effective in reducing negative perceptions of mathematics by creating a more interactive and enjoyable learning environment. In conclusion, the implementation of GBL is an innovative learning strategy that effectively enhances learning motivation and contributes to improving the quality of mathematics education